2021
DOI: 10.21037/tlcr-21-561
|View full text |Cite
|
Sign up to set email alerts
|

Mobile 3-dimensional (3D) C-arm system-assisted transbronchial biopsy and ablation for ground-glass opacity pulmonary nodules: a case report

Abstract: Identification of pulmonary ground-glass opacity (GGO) lesions during bronchoscopic procedures remains challenging, as GGOs cannot be directly visualized under 2-dimensional (2D) fluoroscopy and are often difficult to detect by radial endobronchial ultrasound. Recently, a mobile 2D/3D C-arm fluoroscopy system was developed that provides both 2D fluoroscopy and mobile 3D imaging to assess and confirm the location of the lesions and ancillary bronchoscopic tools. However, previous studies focused mainly on exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Until recently, the use of navigation bronchoscopy to guide flexible ablation probes to the lung periphery had been suboptimal in part due to limitations of localization and in part due to difficulties using rigid probes. Case series describing advanced navigation technologies coupled with MWA and RFA flexible probes have been recently described and are being further investigated [37 ▪ ,38 ▪ ]. Utilizing experience with percutaneous ablation, the efforts in bronchoscopic peripheral ablation now center on confirmation of the location (i.e., tool-in-lesion) by the use of confirmatory imaging (i.e., CBCT or 3D fluoroscopy) as well as confirmation of the ablation zone.…”
Section: Ablation Techniquesmentioning
confidence: 99%
“…Until recently, the use of navigation bronchoscopy to guide flexible ablation probes to the lung periphery had been suboptimal in part due to limitations of localization and in part due to difficulties using rigid probes. Case series describing advanced navigation technologies coupled with MWA and RFA flexible probes have been recently described and are being further investigated [37 ▪ ,38 ▪ ]. Utilizing experience with percutaneous ablation, the efforts in bronchoscopic peripheral ablation now center on confirmation of the location (i.e., tool-in-lesion) by the use of confirmatory imaging (i.e., CBCT or 3D fluoroscopy) as well as confirmation of the ablation zone.…”
Section: Ablation Techniquesmentioning
confidence: 99%
“…Both Avasarala et al ( 8 ) and Sadoughi et al ( 7 ) reported successful transbronchial biopsy of lung nodules using a mobile 3D C-arm system. Chen et al ( 9 ) demonstrated the feasibility and clinical value of the mobile 3D C-arm system for assisting transbronchial biopsy and ablation of GGN lesions. Although Hsieh et al ( 10 ) were the first to report clinical experience with the mobile 3D C-arm system for preoperative pulmonary nodule localization, our team improved the process by using a series of more optimized localization protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mobile CBCT system has disadvantages over the fixed CBCT system in terms of scanning speed, image quality and imaging range, it is adequate for most interventions for pulmonary nodules. Whether in biopsy, localization, or ablation, the mobile CBCT can conveniently provide real‐time 3D images to identify the relationship between tools and target lesion 25,30,73–75 . Some ground‐glass opacity nodules may be difficult to visualize due to the presence of instruments such as metal markers or needles in the surrounding area 28 .…”
Section: Clinical Application Recommendationsmentioning
confidence: 99%
“…In transbronchial or percutaneous transthoracic procedures, CBCT (with fixed C‐arm or mobile C‐arm) delineates positions of the target lesion and the tool in real time, and provides fluoroscopic monitoring during the procedure 25–27 . In ablation procedures, CBCT can also be used for treatment monitoring and evaluating ablation efficacy 28–30 . Some CBCT systems can provide augmented fluoroscopy to guide the tools to target lesions 31–33 .…”
Section: Introductionmentioning
confidence: 99%